Morphoanatomical Changes in Eucalyptus grandis Leaves Associated with Resistance to Austropuccinia psidii in Plants of Two Ages - Furtado, Edson Luiz [UNESP]; Silva, André Costa da; Silva, Érica Araújo Rodrigues; Rodella, Roberto Antônio [UNESP]; Soares, Marcus Alvarenga; Serrão, José Eduardo; de Pieri, Cristiane [UNESP]; Zanuncio, José Cola (MDPI, 2023)
The fungus Austropuccinia psidii infects young tissues of Eucalyptus plants until they are two years old in the nursery and field, causing Myrtaceae rust. The characteristics making older eucalypt leaves resistant to A. psidii and the reason for the low levels of this pathogen in older plants need evaluations. The aim of this study was to evaluate the morphological differences between Eucalyptus grandis leaves of different growth stages and two plant ages to propose a visual phenological scale to classify E. grandis leaves according to their maturation stages and to evaluate the time of leaf maturation for young and adult plants. A scale, based on a morphological differentiation for E. grandis leaves, was made. The color, shape and size distinguished the leaves of the first five leaf pairs. Anatomical analysis showed a higher percentage of reinforced tissue, such as sclerenchyma-like tissue and collenchyma, greater leaf blade thickness, absence of lower palisade parenchyma in the mature leaves and a higher number of cavities with essential oils than in younger ones. Changes in anatomical characteristics that could reduce the susceptibility of older E. grandis leaves to A. psidii coincide with the time of developing leaf resistance. Reduced infection of this pathogen in older plants appears to be associated with a more rapid maturation of their leaf tissues.
Keywords: anatomy; eucalypts; leaf maturation scale; leaf stages; morphological markers; Myrtaceae rust; ontogenic resistance